Smart material for anti-counterfeit and temperature indicator applications - Jackson (Nanyang Technological University, 2021)
This project aims to use low cost and recyclable material to make anti-counterfeit labels by using shape memory polymers. Shape memory polymers are polymeric smart materials that are able to display shape memory effects. The process of using heat as a stimulus will change the shape of the shape memory polymer and become easily deformative. This highly thermally conductive material is found to be suitable for food packaging as sterilisation and heat treatment is essential in its process. Additionally, Thermochromic pigments are being discovered to transform into another colour at a specific temperature. There are two types of these thermochromic crystals - reversible and irreversible crystals. They are suitable to be used for temperature change indicators. The future use of this material for other applications is being explored.